2016
DOI: 10.1111/cod.12656
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported hand eczema among dental workers in Japan – a cross‐sectional study

Abstract: Dental workers in Japan have a high prevalence of hand eczema. Health education to prevent hand eczema and more frequent patch testing are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 35 publications
2
42
1
5
Order By: Relevance
“…As reported in our previous study on dental workers, their clinical pictures were mostly erythema and dryness (66%), while localizations were predominantly on the hands and fingers (96%) [16]. According to the study by Minamoto et al [12], 46.4% of dental workers reported a lifetime history of chronic hand eczema, which was commonly related to a history of AD, asthma/allergic rhinitis, dry skin, shorter duration of work, and hand washing (> 10 times/day). Our results were somewhat similar and indicated peak lesion incidence at the beginning and end of a professional career.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…As reported in our previous study on dental workers, their clinical pictures were mostly erythema and dryness (66%), while localizations were predominantly on the hands and fingers (96%) [16]. According to the study by Minamoto et al [12], 46.4% of dental workers reported a lifetime history of chronic hand eczema, which was commonly related to a history of AD, asthma/allergic rhinitis, dry skin, shorter duration of work, and hand washing (> 10 times/day). Our results were somewhat similar and indicated peak lesion incidence at the beginning and end of a professional career.…”
Section: Discussionmentioning
confidence: 50%
“…According to the patch test results of Schwensen et al [22] (thiuram mix, mercaptobenzothiazole, mercapto mix), this contact allergy was found in 3.1% (often to thiuram mix) and was significantly associated with occupational CD, hand and facial dermatitis, and age (> 40 years). According to the patch testing of dental workers by Minamoto et al [12], the most frequent occupationally relevant contact allergens were rubber chemicals and acrylates. Because of the limited conditions of our field study and its implementation, we did not research other common allergens in today's dental work environment (acrylates and methacrylates used in dental prostheses, dental restoration materials, antiseptic agents, and disinfectants, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the present results, previous studies showed a significant difference in atopic dermatitis, allergic conjunctivitis, asthma, and childhood eczema. [30] Another study reported that atopic history played a role in the development of dermatitis in work setting. [31] Consistent with the present results, another study reported an insignificant correlation between hand eczema and asthma or childhood eczema in car mechanics.…”
Section: Discussionmentioning
confidence: 99%
“…HE is often work‐related, with a high prevalence especially in occupations involving wet work, such as nursing, medical and service work . In Japan, three population‐based studies have been performed . The 1‐year prevalence of HE in those Japanese studies, which were performed in an occupational setting, was reported to be much higher than the estimated prevalence of 10% found in the general population .…”
Section: Introductionmentioning
confidence: 99%